EDUKASI MP-ASI DENGAN MEDIA BOOKLET TERHADAP PENGETAHUAN IBU BALITA MENYIAPKAN MP-ASI DI WILAYAH KERJA PUSKESMAS RAMBATAN I - Rifdi, Febriniwati; Dini, Firma (Maternal Child Health Care, 2024)
According to the data from Rambatan Community Health Center from January to August 2023 showed that 105 toddlers suffered from malnutrition. One of the nutritional problems among toddlers is due to the insufficient knowledge of mothers in preparing complementary feeding (MP ASI). Therefore, education through booklet media is needed to improve the knowledge of mothers in preparing for MP ASI. This study aims to determine the influence of MP ASI education through booklet media on the knowledge of mothers with toddlers in preparing MPASI in the working area of Rambatan Community Health Center I, Tanah Datar. This quasi-experimental research employed a one-group pretest and post-test design. The research was conducted in the working area of RambatanCommunity Health Center, with data collection taking place in February 2024. The sample was selected through purposive sampling, and data were collected using questionnaires. Data analysis involved univariate and bivariate analysis using the Wilcoxon test with a 95% confidence level. The research results revealed that before the education, the average pretest knowledge score of respondents was 13.53, and the post-test score was 17.60. There was a significant influence of education using booklet media on the knowledge (p=0.000) of mothers with toddlers in the working area of RambatanCommunity Health Center. In conclusion, the booklet media was effective in improving the knowledge of mothers in preparing MPASI in the working area of RambatanCommunity Health Center. It is recommended that the nutrition and maternal and child health program departments of RambatanCommunity Health Center develop periodic education programs on providing MPASI at integrated health posts to enhance the knowledge of mothers in preparing MP ASI.